Saudi Arabia’s Shaken Pillars: Impact on Southeast Asian Muslims - Saleem, Saleena (2016)
Recent geopolitical developments in the Middle East have shaken Saudi Arabia’s long-standing ideational “pillars” that underpin its domestic and foreign policies. For Muslims in Southeast Asia where Saudi Arabian soft power influence is relatively significant, the developments can create the conditions for a fragmentation of the Sunni Muslim landscape.